2015
DOI: 10.4172/2153-2435.1000401
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Terahertz Time-Domain and Low-Frequency Raman Spectroscopy of Crystalline and Glassy Pharmaceuticals

Abstract: The applications of the broadband Terahertz Time-Domain Spectroscopy (THz-TDS) and the low-frequency Raman scattering spectroscopy to glassy and crystalline pharmaceuticals were reviewed. The real and imaginary parts of a complex dielectric constant were measured by the transmission of THz-TDS using a pure pellet without mixing polyethylene in the frequency range from 0.2 to 6.5 THz. The low-frequency Raman spectra were measured down to 0.3 THz using a double-grating spectrometer. In crystalline indomethacin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…These phase transitions were monitored in the low-frequency THz-Raman spectral region that covers the Stokes signal (5–200 cm –1 ) and provides information about the crystal lattice vibration (phonon) modes. 34,35 Such vibrations are sensitive to local order and disorder, enabling distinction between different crystal packing arrangements, including the amorphous and crystalline states. 36,37…”
Section: Resultsmentioning
confidence: 99%
“…These phase transitions were monitored in the low-frequency THz-Raman spectral region that covers the Stokes signal (5–200 cm –1 ) and provides information about the crystal lattice vibration (phonon) modes. 34,35 Such vibrations are sensitive to local order and disorder, enabling distinction between different crystal packing arrangements, including the amorphous and crystalline states. 36,37…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that these polyhydric alcohols [71] have a linear frequency dependence on C IR (ν). On the other hand, the pharmaceutical IMC glass, which is also a hydrogenbonded organic glass, shows a significant discrepancy between ν BP−IR [8,9] and ν BP−Raman [8,9,81], and ν BP−IR /ν BP−Raman ∼ 0.6 [8,9,81]. The different tendency of the ratio from the polyhydric alcohols suggests that C IR (ν) of IMC will obey Taraskin's model.…”
Section: Relative Light-vibration Coupling Coefficientmentioning
confidence: 99%
“…Numerous studies have been done regarding the BP dynamics; however, the microscopic origin is not yet fully understood. Furthermore, there have been almost no recent THz spectroscopic studies of the BP dynamics reported [6][7][8][9][10], in spite of advanced development of the technique of the THz light source and detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this chapter, Recent progress of terahertz vibrational spectroscopy using THz-time-domain spectroscopy (THz-TDS) [3], THz time-domain spectroscopic ellipsometry (THz-TDSE) [4], and far-infrared spectroscopy is reviewed in advanced materials science on the following three kinds of materials. (1) Pharmaceuticals: studies of terahertz vibrational spectroscopy on polymorphism of crystalline states and glassy states on typical pharmaceuticals [5]. (2) Ferroelectric materials: studies of terahertz vibrational spectroscopy on optical phonons, ferroelectric soft mode, and phonon-polariton dispersion relation on typical ferroelectric crystals for optical application [6].…”
Section: Introductionmentioning
confidence: 99%